Legal Certainty of Consumer Dispute Resolution Agency Decisions That Exceed the Dispute Resolution Deadline - Faizah, Syarifah; Marina, Liza; Sunarsi, Dessy (Batulis Civil Law Review, 2026)
Introduction: The Consumer Dispute Resolution Agency is mandated under Law Number 8 of 1999 Concerning Consumer Protection to resolve consumer disputes within 21 working days as stipulated in Article 55. However, in practice, several Consumer Dispute Resolution Agency decisions exceed this statutory time limit, raising questions regarding legal certainty and the validity of such decisions. This issue reflects normative inconsistencies and practical obstacles in the implementation of consumer dispute resolution mechanisms in Indonesia. Purposes of the Research: This study aims to analyze the legal certainty of Consumer Dispute Resolution Agency decisions rendered beyond the 21-working-day time limit under Article 55 of the Consumer Protection Act and to identify the obstacles causing such delays, along with the proposed solutions. Methods of the Research: This research employs a normative-empirical juridical method with a descriptive-analytical approach. Data were collected through library research and field research, including interviews with members of Consumer Dispute Resolution Agency in Bogor City and Bogor Regency. Results Main Findings of the Research: The findings indicate that Consumer Dispute Resolution Agency decisions issued beyond the statutory time limit lack legal certainty and may be considered legally flawed or null and void due to non-compliance with Article 55 of the Consumer Protection Act. The obstacles contributing to delays stem from internal factors, such as limited human resources with legal backgrounds and the absence of a specific procedural law, as well as external factors, including the non-attendance of disputing parties and difficulties in reaching agreements. The study recommends revising the Consumer Protection Act to strengthen BPSK’s institutional authority, standardize procedural regulations (including verification and validation mechanisms), and improve the quality and accountability of its human resources.